Factors Associated with Goiter Incidence in Farmers in Kismantoro Sub-District, Wonogiri Regency - Ahshaina Ramadhaningtiyas; Yulia Lanti Retno Dewi; Sugihardjo Sugihardjo (Amerta Nutrition, 2022)
Background: Kismantoro Sub-district has been an endemic area of ​​severe goiter since 1982, with a total goiter rate of 35.5% until 2007, when was declared a mild endemic goiter area (TGR 10.79%). Monitoring in 2017 on salt circulating in Wonogiri exposed that there were still 26.01% of brands that did not meet the Indonesian national standard. Objective: This study aimed to analyze the factors associated with goiter incidence in Kismantoro Sub-district, Wonogiri Regency. Methods: This research applied analytic observational with a case-control design. The samples were 41 respondents in the case group and 41 respondents in the control group, taken by purposive sampling. The history of goiter was obtained from the medical records of Kismantoro Community Health Center. The data analysis method employed was logistic regression analysis. Results: The results showed a significant correlation between age (p 0.005, OR 5.88, 95%CI 1.53-22.62), gender (p 0.003, OR 0.15, 95%CI 0.04-0.58), and salt iodine content (p 0.007, OR 0.14, 95%CI 0.03-0.68) with the goiter incidence in farmers in Kismantoro. Moreover, the multiple logistic regression test results revealed that age was the most dominant variable influencing the goiter incidence (p 0.006, OR 8.103, 95%CI (1.799-36.499). Conclusion: There was a relationship between age and the goiter incidence, gender with the goiter incidence, and iodine content in household salt with the goiter incidence, the multiple logistic regression test results indicated that the age variable most influenced goiter incidence among farmers in Kismantoro Sub-District, Wonogiri Regency.